Literasi numerasi ditinjau dari self regulated learning dengan problem based learning berbantuan liveworksheet - Husna, Nurya Maulida; Isnarto, Isnarto; Suyitno, Amin (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2024)
Numeracy literacy skills are very important in solving problems in the current era. In learning, a learning model and the role of the teacher are needed when teaching students about Self Regulated Learning. This research aims to describe students' numeracy literacy in terms of Self Regulated Learning with the Problem-Based Learning model assisted by Liveworksheets. The research method used is descriptive qualitative. This research was carried out at SMP IT Al Fateeh Semarang by 25 class VIII students, subject selection was based on the results of a questionnaire. From the sequence of questionnaire scores, researchers can determine which students are in the high category, medium category, and low ability category. Based on the test results, 6 research subjects were chosen to represent students in the categories of high, medium, and low self-regulated learning abilities. The subjects were interviewed by the researcher based on how to solve the SPLDV material description test questions. The research subjects consisted of six students representing three levels of Self Regulated Learning (low, medium, high) in the experimental class as research subjects. Based on the results of the analysis of answers and interviews with research subjects, it was found that students with a low level did not meet all the indicators of numeracy literacy, students with a moderate level of Self Regulated Learning met the indicators of understanding problems, using mathematical rules, strategies for interpreting symbols. Students with a high level of Self Regulated Learning fulfill all indicators of understanding problems, using mathematical rules, and strategies for solving problems, and being able to interpret symbols and draw conclusions.